Banking Chatbot (B-Bot - et. al., Dr. C. Punitha Devi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Chatbots square measure intelligent systems that perceive a user's tongue queries and respond consequently during a conversation, that is the focus of this study. It's an additional sort of a virtual assistant, folks want they're talking with a real person. They speak a constant language we have a tendency to do, and will answer all queries. In banks, at customer care centers and enquiry desks, humans are lean and usually take very long time to method the only request which ends up in wastage of your time and additionally cut back quality of client service. In this paper we introduce a more efficient way to resolve customer queries. Today’s customers have high expectations and they want quick and accurate responses, complete and robust resolution, service that is available anywhere and anytime. All of these can be within well-designed chatbots. The entire experience is conversational. The aim is to implement a chatbot which may resolve client queries, search the knowledgebase for resolution and provide the solution. The chatbot can handle the queries ultimately reducing human effort.